Crack propagation and effect of mixed oxides on TGO growth in thick La-Gd-YSZ thermal barrier coating - Mahalingam S.; Yunus S.M.; Manap A.; Afandi N.M.; Zainuddin R.A.; Kadir N.F. (MDPI AG, 2023)
Thick thermal barrier coatings (TBCs) are the main choice in the aviation industry due to their ability to handle elevated temperature exposure in turbines. However, the efficacy of thick TBCs has not been adequate. This study presents a highly durable, thick top-coat (TC) of Lanthanum-gadolinium-yttria stabilized zirconia (La-Gd-YSZ) on high-velocity oxygen fuel (HVOF)-bond coat (HVOF-BC). Crack propagation was quantitatively assessed using a three-dimensional (3D) measuring laser microscope due to higher reliability in calculating the actual crack length of TBC. The findings revealed the HVOF-BC is highly durable with intact structural composition, while the conventional TBC of atmospheric plasma spraying (APS) bond coat (APS-BC) of the same composition and thickness with identical TC was detached at a crack-susceptible zone. The significant enhancement in HVOF-BC is due to the low mixed-oxides growth rate in thermally grown oxide (TGO) with a uniform and dense protective layer of stable Al2O3 which reduces crack propagation. Meanwhile, the failure in APS-BC can be attributed to the high TGO growth rate and thickness with segmented and unstable Al2O3. Furthermore, detrimental mixed oxides such as spinel Ni(Cr,Al)2O4 and NiO lead to disastrous horizontal and compressive cracks. To that end, we study the effect of TGO growth and crack propagation on HVOF-BC TBCs using APS-BC TBCs as a reference. 2019 by the authors.